Government-Led DMO And Collaborative Governance Practices: Case Study In Labuan Bajo, Flores, Indonesia - Fransiskus Xaverius Teguh; Noel Scott (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
Sustainable tourism in island destinations requires governance approaches that balance ecological preservation, community well-being, and economic development. The present study examines the collaborative governance practices of the Tourism Authority Board in Labuan Bajo, Flores, Indonesia, a government-led Destination Management Organisation (DMO). Employing a qualitative case study design, data were collected through semi-structured interviews with informants representing government agencies, private sector actors, local communities, NGOs, and media, complemented by document analysis and field observations across Komodo National Park, Labuan Bajo, and surrounding areas in Flores, Lembata, and Alor. The findings indicate that the Board effectively coordinates across multiple agencies and jurisdictions, aligning national and regional tourism strategies. However, community stakeholders report limited influence in decision-making process. Mechanisms such as multi-stakeholder workshops, regional forums, and community networks facilitate local participation and adaptive governance. The study proposes a hybrid institutional model integrating participatory governance, cross-sector coordination, and transformational leadership, enhancing policy coherence, stakeholder engagement, and sustainable tourism outcomes. The research demonstrates that government-led DMOs can act as orchestrators of inclusive and adaptive governance, bridging centralized authority with local priorities in complex island  tourism destination systems.